Sudden cardiac arrest in the field in an 18-year-old male athlete with Noonan syndrome: case presentation and 5-year follow-up. (5th August 2019) - Petrin, Ziva; Soffer, Benjamin; Daniels, Steven J.
Abstract: We present a case of sudden cardiac arrest in the field with complete neurological recovery in an 18-year-old athlete with phenotypic Noonan syndrome. Evaluation revealed interventricular septal thickness of 18 mm without left ventricular outflow tract obstruction and no other identifiable structural, electrophysiologic, or genetic abnormality except isolated heterozygous variant for desmoplakin DSP variant p.Lys2103Glu, with unknown clinical significance.